Efforts to Improve Teacher Competence in Learning Implementation Plans (RPP) Through Academic Supervision at SMK Negeri 8 Bungo: Upaya Meningkatan Kompetensi Guru Dalam Menyusun Rencana Pelaksanaan Pembelajaran (Rpp) Melalui Supervisi Akademik di SMK Negeri 8 Bungo - Hanura (International Journal of Technology Vocational Education and Training, 2021)
This research is motivated by the low ability of teachers, especially at SMK Negeri 08 Bungo in preparing lesson plans used in the learning process. Each process must always include three main activities, namely planning, implementation and evaluation. The same is true of the learning process in schools. A teacher is required to plan, implement and evaluate learning. learning planning process that must be carried out by teacher includes main activities including: making an annual program, making a syllabus, making a semester program, making a Learning Implementation Plan (RPP), and making a test/evaluation program. Of the five elements mentioned above, RPP is the minimum preparation for a teacher when teaching in class. Based on the results of the analysis of learning planning in the 2020/2021 school year at SMK Negeri 8 Bungo, there is a problem with the low number of teachers who make lesson plans, especially the preparation of lesson plans. To examine the weakness of teacher performance in this regard, study was conducted to see what extent the principal's academic supervision measures can improve teacher competence in the preparation of Learning Implementation Plans. research method used in this research is school action research (PTS) which consists of planning, action, observation and reflection. Data collection techniques using written assignments and observation sheets. The results showed that academic supervision carried out in each cycle through School Action Research was able to improve the ability of teachers in preparing lesson plans